Ophelia - Schubert, Ingrid; Schubert, Dieter, 1947- (Honesdale, Penn : Lemniscaat, 2009)
As Ophelia rushes to comfort her friend Kevin, who is suffering from butterflies in the stomach, she meets up with various friends who misunderstand the problem, each one adding a new ailment and cure to the growing list.
Originally published: Netherlands : Lemniscaat b.v. Rotterdam, 2008.
Keywords: Sick; Animals; Friendship; Sick; Animals; Friendship